Linear effects of increasing weaning age in three-site production - R G Main; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2002)
Two studies were conducted to measure the biologic and economic effects of weaning age in a three-site production system. Wean-to-finish growth and financial performance improved linearly as weaning age increased up to 21.5 days. Data from these trials were modeled to determine the linear rates of improvement observed as weaning age increased from 15 to 21.5 days. Each day increase in weaning age increased initial weight (taken prior to weaning) 0.565 ± 0.009 lb and weight sold to slaughter 3.71 ± 0.32 lb per pig weaned. In the financial analysis, income over cost increased 0.94 ± 0.07 per wean age d in the limited finishing space scenario and 0.53 ± 0.06 per wean age d in the non-limited space scenario. Therefore, if finishing space is limited, increasing weaning age from 16 to 19 d is predicted to improve income over cost by 2.82 per pig. These rates of improvement can be used to model the effects of weaning age on wean-to-finish throughput and financial performance in a three-site production system.; Swine Day, Manhattan, KS, November 14, 2002
Keywords: Swine day; 2002; Kansas Agricultural Experiment Station contribution; no. 03-120-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 897; Weaning age; Throughput; Economics; Swine